1994
DOI: 10.1086/174036
|View full text |Cite
|
Sign up to set email alerts
|

Power-spectrum analysis of three-dimensional redshift surveys

Abstract: We develop a general method for power spectrum analysis of three dimensional redshift surveys. We present rigorous analytical estimates for the statistical uncertainty in the power and we are able to derive a rigorous optimal weighting scheme under the reasonable (and largely empirically verified) assumption that the long wavelength Fourier components are Gaussian distributed. We apply the formalism to the updated 1-in-6 QDOT IRAS redshift survey, and compare our results to data from other probes: APM angular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,201
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 942 publications
(1,220 citation statements)
references
References 22 publications
16
1,201
0
3
Order By: Relevance
“…Tegmark et al (2006) analyzed the DR4 LRG and main galaxy samples with a quadratic estimator for the power spectrum and redshiftspace distortion. Hütsi (2006) analyzed the monopole of the power spectrum of the LRG data set with the Feldman et al (1994) (FKP) method. Percival et al (2007) applied the FKP method to the combined DR5 LRG and main galaxy samples, along with the 2dFGRS sample, to measure the acoustic scale at two different redshifts (z = 0.20 and 0.35).…”
Section: The Current State Of Playmentioning
confidence: 99%
“…Tegmark et al (2006) analyzed the DR4 LRG and main galaxy samples with a quadratic estimator for the power spectrum and redshiftspace distortion. Hütsi (2006) analyzed the monopole of the power spectrum of the LRG data set with the Feldman et al (1994) (FKP) method. Percival et al (2007) applied the FKP method to the combined DR5 LRG and main galaxy samples, along with the 2dFGRS sample, to measure the acoustic scale at two different redshifts (z = 0.20 and 0.35).…”
Section: The Current State Of Playmentioning
confidence: 99%
“…Here we will summarise these measurements but refer to the above mentioned references for more details. The first three non-zero power spectrum multipoles can be calculated as (Feldman, Kaiser & Peacock 1994) …”
Section: Boss Measurements and Uncertaintiesmentioning
confidence: 99%
“…The fact that we have to estimate the mean density of galaxies from the sample itself means that the k = 0 mode is artificially set to zero, equivalent to subtracting a single Dirac delta function from the centre of the un-convolved power. The equivalent correction for correlation function estimates is commonly know as the "Integral constraint" The comoving power spectrum, as measured from the Data Release 9 (DR9) BOSS data, using the Feldman et al (1994) technique is shown in Fig. 3.…”
Section: Measuring the Power Spectrummentioning
confidence: 99%